Evaluating the Level of Adherence To The Ministry Of Health Guideline In The Management Of Severe Acute Malnutrition at Adama Hospital Medical College; A Cross-Sectional Study - Bidu, Kassahun Tegegne; Ebiyo, Derartu Hailu; Assegu, Yirga Bieza; Bekele, Esulalem Abebe; Heyi, Sadat Kasim (British Journal of Healthcare and Medical Research, 2024)
Background: Severe Acute Malnutrition (SAM) is defined as a weight-for-height (WFH) of < -3 standard deviations or MUAC of < 11.5cm, or bilateral pitting edema among under-five children. WHO developed 10 steps with evidence generated from multiple countries to reduce case fatality rate among SAM cases but their implementation and impact on case fatality locally remain unknown. Objective: To evaluate the level of adherence to MOH guidelines in the management of SAM children. Methods: Descriptive cross-sectional study with systematic sampling techniques was conducted from November 1st to 30th, 2023 on medical records of SAM cases. Data analysis done using statistical package for social sciences (SPSS) version 25. Results: Of 200 SAM cases, 103 (51.5%) were female and mean age and SD were 23.56 + 11.93 months. The average length of stay in the hospital was 13.6 days. Overall adherence to MOH guidelines was 15.5%, and the appropriateness of treatment in the management was: Step 1: 20.5%; Step 2: 65.5%; Step 3: 32%; Step 4: 28.5%; Step 5: 41.5%; Step 6: 34%; Step 7: 35%; and Step 8: 39%. Treatment outcome for SAM cases were: stabilized to OTP, cured, transferred out, non-responder, defaulter, and died were 63%, 20%, 2.5%, 2.5%, 2%, and 0%, respectively. Conclusion and Recommendations: Adherence level to MOH guidelines was low at 15.5% and approprieteness for step of management ranges from 20.5 to 65.5%. Thus, improving adherence to MOH guidelines in SAM management and further studies to determine factors affecting adherence and length of hospital stay need to be conducted.